Depending of thermophysical properties of clay on concerntation of some heavy metals (2011)
"This paper presents the relationship between thermo physical properties (thermal conductivity and thermal diffusivity) and heavy metal concentration of some surface clay from six local governments in Ibadan, Oyo state, Nigeria. An atomic absorption spectrometer (AAS) was used in analyzing the concentration of heavy metals present in each sample by measuring the intensity of external radiation absorbed by the atom produced from the same sample at a wavelength characteristic to that element. A transient measurement technique was wed to determine the thermal conductivity and thermal diffusivity. Thermal conductivity of each sample was compared with the concentration of heavy metals present in the sample. Based on the results obtained from AAS, Manganese has the highest concentration in all the samples. It was followed by Zinc and the least was lead. The values of temperature, time and their respective measured thermal conductivity were highly correlated; with correlation coefficients between 0.9 and 1. "